Associations between different types and sources of dietary fibre intake and depressive symptoms in a general population of adults: a cross-sectional study. Issue 11 (14th June 2021) - Xia, Yang; Liu, Yashu; Zhang, Shunming; Zhang, Qing; Liu, Li; Meng, Ge; Wu, Hongmei; Sun, Shaomei; Wang, Xing; Zhou, Ming; Jia, Qiyu; Song, Kun; et al.
Abstract: This cross-sectional study aimed to examine the associations between dietary fibre (DF) intake and depressive symptoms in a general adult population in Tianjin, China. A total of 24 306 participants (mean age 41 years; range 18–91 years) were enrolled. DF intake was assessed using a validated self-administered FFQ. Depressive symptoms were assessed using the Self-Rating Depression Scale. Associations between DF intake and depressive symptoms were estimated using logistic regression analysis. Socio-demographic, behavioural, health status and dietary factors were adjusted. In men, compared with participants in the lowest quartiles for total, soluble, vegetable and soya DF, OR for depressive symptoms in the highest were 0·83 (95 % CI 0·69, 0·99), 0·74 (95 % CI 0·63, 0·87), 0·79 (95 % CI 0·65, 0·96) and 0·69 (95 % CI 0·60, 0·81), respectively. In women, compared with participants in the lowest quartiles for vegetable and soya DF, the OR for depressive symptoms in the highest were 0·77 (95 % CI 0·64, 0·93) and 0·82 (95 % CI 0·70, 0·95), respectively. No association was found between total or soluble DF intake and depressive symptoms in women. No association was found between insoluble, cereal, fruit or tuber DF intake and depressive symptoms in men and women. Linear associations between DF intake and depressive symptoms were only detected for soya DF (men, β = –0·148, P < 0·0001; women, β = –0·069, P = 0·04). Results suggest that intake of soluble, vegetable and soya DF was inversely associated with depressive symptoms. These results should be confirmed through prospective and interventional studies.